Mode of presentation and skin thickening on ultrasound may predict nodal burden in breast cancer patients with a positive axillary core biopsy - Choong, Wen Ling (Br J Radiol, 2020)
OBJECTIVE: A number of pre-operative factors predicting nodal burden in females with breast cancer have recently been identified. The aim of this study is to assess if these factors independently influence nodal burden in females with a positive axillary core biopsy. METHODS: All node positive patients detected on axillary core biopsy were identified in our cancer audit database. Mode of presentation, age, core tumour grade, core tumour type, ER and HER2 status were evaluated. Tumours were assessed for ultrasound size, distance of tumour-to-skin, presence of invasion of skin and diffuse skin thickening. Axillary lymph nodes were assessed for cortical thickness and presence of ultrasound replaced nodes. Statistical significance was ascertained using univariate logistic regression. A predictive model was produced following a multiple logistic regression model incorporating cross-validation and assessed using receiving operating characteristic curve. RESULTS: 115 patients’ data were analysed. Patients referred because of symptoms (70% vs 38%, p = 0.005), and those with ultrasound skin thickening (87% vs 59%, p = 0.055) have higher nodal burden than those referred from screening or without skin thickening. These factors were significant after multivariate analysis. The final predictive model included mode of presentation, ultrasound tumour size, cortical thickness and presence of ultrasound skin thickening. The area under curve is 0.77. CONCLUSION: We have shown that mode of presentation and ultrasound skin thickening are independent predictors of high nodal burden at surgery. A model has been developed to predict nodal burden pre-operatively, which may lead to avoidance of axillary node clearance in patients with lower nodal burden. ADVANCES IN KNOWLEDGE: Method of presentation and skin involvement/proximity to skin by the primary tumour are known to influence outcome and nodal involvement respectively but have not been studied with regard to nodal burden. We have shown that mode of presentation and skin thickening at ultrasound are independent predictors of high nodal burden at surgery.